2014
DOI: 10.18632/oncotarget.1921
|View full text |Cite
|
Sign up to set email alerts
|

Oncolytic reovirus preferentially induces apoptosis in KRAS mutant colorectal cancer cells, and synergizes with irinotecan

Abstract: Reovirus is a double stranded RNA virus, with an intrinsic preference for replication in KRAS mutant cells. As 45% of human colorectal cancers (CRC) harbor KRAS mutations, we sought to investigate its efficacy in KRAS mutant CRC cells, and examine its impact in combination with the topoisimerase-1 inhibitor, irinotecan. Reovirus efficacy was examined in the KRAS mutant HCT116, and the isogenic KRAS WT Hke3 cell line, and in the non-malignant rat intestinal epithelial cell line. Apoptosis was determined by flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 29 publications
(43 reference statements)
2
49
0
Order By: Relevance
“…Irinotecan has been shown to inhibit HSV-1 viral replication and lytic oncolysis in colon cancer cell lines 164. In contrast, other groups show synergy with OVs/irinotecan, including HSV-1 encoding CYP2B1,127 reovirus,128 and Sindbis virus 126. However, only the study on Sindbis virus looked at immune components in irinotecan synergy, concluding that natural killer cells are essential for the process 126…”
Section: Combining Chemotherapeutic Drugs With Ov Therapymentioning
confidence: 99%
“…Irinotecan has been shown to inhibit HSV-1 viral replication and lytic oncolysis in colon cancer cell lines 164. In contrast, other groups show synergy with OVs/irinotecan, including HSV-1 encoding CYP2B1,127 reovirus,128 and Sindbis virus 126. However, only the study on Sindbis virus looked at immune components in irinotecan synergy, concluding that natural killer cells are essential for the process 126…”
Section: Combining Chemotherapeutic Drugs With Ov Therapymentioning
confidence: 99%
“…In EGFR‐, Sos‐, or ras ‐transformed cells, PKR is held in a nonphosphorylated state, and the replication of the reovirus proceeds uninhibited . The dependence of reovirus activity on activation or mutation of the Ras pathway may be indication‐specific …”
Section: Introductionmentioning
confidence: 99%
“…6 The dependence of reovirus activity on activation or mutation of the Ras pathway may be indicationspecific. 7,8 A reovirus administered with paclitaxel was synergistic in all NSCLC cell lines examined, including those with high-level resistance to paclitaxel or the reovirus. 9 Phase 1 clinical trials involving Reolysin dispensed as a monotherapy or in combination with gemcitabine, cyclophosphamide, docetaxel, or paclitaxel and carboplatin demonstrated its good tolerability as monotherapy (mild to moderate flulike symptoms and gastrointestinal symptoms were the major side effects) and a lack of exacerbation of the toxicities of the chemotherapeutic agents when it was given in combination.…”
Section: Introductionmentioning
confidence: 99%
“…As with the vast majority of cancer therapies, OVs are unlikely to be delivered alone but rather as part of a rationally designed, combination therapy regimen (Ottolino‐Perry et al., 2010). OVs have been combined with surgical resection (Acuna et al., 2014; Gholami et al., 2013; Nakano et al., 2005; Tai et al., 2013), radiation (Advani et al., 2012; Mansfield et al., 2013), and numerous chemotherapy drugs (Cherubini et al., 2011; Gutermann et al., 2006; Heinemann et al., 2011; Huang et al., 2011; Maitra et al., 2014; Takakura et al., 2010; Zaoui et al., 2012; Ziauddin et al., 2010) in preclinical models. Combination OV and chemotherapy studies have demonstrated that particular combinations can be highly synergistic in specific tumour models.…”
Section: Introductionmentioning
confidence: 99%
“…Other platinum‐based agents have also been shown to synergize with VV primarily through enhanced anti‐tumour immune responses (Song et al., 2007; Yu et al., 2009). While CPT‐11 has been demonstrated to interact synergistically with oncolytic herpes simplex virus (Gutermann et al., 2006), adenovirus (Cherubini et al., 2011) and reovirus (Maitra et al., 2014) its effect when combined with oncolytic VV is unknown.…”
Section: Introductionmentioning
confidence: 99%